2011
DOI: 10.1227/neu.0b013e31820b51f3
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, Randomized, Double-Blind Clinical Study Evaluating the Correlation of Clinical Outcomes and Cervical Sagittal Alignment

Abstract: BACKGROUND: Sagittal alignment of the cervical spine has received increased attention in the literature as an important determinant of clinical outcomes after anterior cervical diskectomy and fusion. Surgeons use parallel or lordotically fashioned grafts depending on preference or simple availability. OBJECTIVE: To quantitatively assess and compare cervical sagittal alignment and clinical outcome when lordotic or parallel all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
101
3
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(111 citation statements)
references
References 22 publications
3
101
3
4
Order By: Relevance
“…9 Villavicencio et al conducted a prospective, double-blind, randomized study evaluating the relationship between lordotic alignment and clinical outcomes using normal and lordotically shaped allografts for ACDF. 24 They found that improved cervical Cobb angle alignment was not significantly correlated with clinical outcomes, but that maintaining or improving segmental sagittal alignment was associated with a greater improvement in outcome scores.…”
Section: Discussionmentioning
confidence: 97%
“…9 Villavicencio et al conducted a prospective, double-blind, randomized study evaluating the relationship between lordotic alignment and clinical outcomes using normal and lordotically shaped allografts for ACDF. 24 They found that improved cervical Cobb angle alignment was not significantly correlated with clinical outcomes, but that maintaining or improving segmental sagittal alignment was associated with a greater improvement in outcome scores.…”
Section: Discussionmentioning
confidence: 97%
“…This may indicate that preservation of the cervical lordosis would be more important for the long-term clinical outcome than cage subsidence itself. Normal lordotic alignment is one of the most important factors contributing to good motion and function of the cervical spine [29]. Postoperative kyphosis at a fused cervical motion segment has been reported frequently, especially in uninstrumented anterior fusion [28], with an incidence as high as 27.3% [13].…”
Section: Discussionmentioning
confidence: 99%
“…34 However, the extent to which segmental and/or global sagittal cervical alignment correlates with HRQOL remains controversial, as other studies have not consistently demonstrated similar significant correlations. 16,19,57 Given that cervical kyphosis is the most common type of CSD and that a subset of studies has identified a clinical impact of this kyphosis, a parameter reflective of CL was selected as a modifier for the CSD classification. In deciding on the optimal parameter to include, consideration was given to the relationship between PI and LL.…”
Section: T-1 Slope Minus C2-7 Lordosis Modifiermentioning
confidence: 99%